Ecological stability of Late Pleistocene-to-Holocene Lesotho, southern Africa, facilitated human upland habitation - Patalano, R; Arthur, C; Carleton, WC; Challis, S; Dewar, G; Gayantha, K; Gleixner, G; Ilgner, J; Lucas, M; Marzo, S; Mokhachane, R; Pazan, K; et al. (Springer Nature, 2023)
Investigation of Homo sapiens’ palaeogeographic expansion into African mountain environments are changing the understanding of our species’ adaptions to various extreme Pleistocene climates and habitats. Here, we present a vegetation and precipitation record from the Ha Makotoko rockshelter in western Lesotho, which extends from ~60,000 to 1,000 years ago. Stable carbon isotope ratios from plant wax biomarkers indicate a constant C3-dominated ecosystem up to about 5,000 years ago, followed by C4 grassland expansion due to increasing Holocene temperatures. Hydrogen isotope ratios indicate a drier, yet stable, Pleistocene and Early Holocene compared to a relatively wet Late Holocene. Although relatively cool and dry, the Pleistocene was ecologically reliable due to generally uniform precipitation amounts, which incentivized persistent habitation because of dependable freshwater reserves that supported rich terrestrial foods and provided prime locations for catching fish.